The Influence of Financial Literacy and Business Management on Business Success - Nafisah Suhaila; Rizkha Maulana; Rauzana; Maryana; Mulyadi (CV. Inara in Colaboration with www.stie-sampit.ac.id, 2026)
This research looks at how financial knowledge and management skills affect the success of businesses in Bireuen Regency, which is in Aceh Province. Business success is a key sign of how well a region's economy is doing, but many business people still have trouble with managing money and running their operations smoothly. This study used a quantitative method and conducted a survey. The study included all registered business people at the Department of Cooperatives and SMEs in Bireuen Regency, and 150 people were chosen as participants through a purposeful sampling method. Data was gathered using questionnaires and then examined with multiple linear regression analysis using SPSS 26 software. The findings indicate that financial literacy has a positive and significant impact on business success (β = 0.412; t = 4.873; p < 0.05), and business management also has a positive and significant effect on business success (β = 0.387; t = 4.521; p < 0.05). When both financial literacy and business management are considered together, they have a combined significant effect on business success (F = 48.672; p < 0.05), and they explain 57.3% of the variation in business success. This suggests that when business people in Bireuen Regency have better knowledge about money and stronger skills in managing their businesses, it greatly helps them achieve success.